UJI AKTIVITAS ANTIBAKTERI EKSTRAK TUMBUHAN Euphorbia hirta L. TERHADAP Ralstonia solanacearum, Escherichia coli, DAN Staphylococcus aureus SECARA IN VITRO - Genoveva Preta Angelika; Agung Suprihadi; Sri pujiyanto (Jurnal Akademika Biologi, 2014)
Biocontrol using Patikan kebo (Euphorbia hirta L.) plant is an alternative solution to control pathogenic bacteria. Such wild plant is known to contain active compounds with antibacterial activity such as tannins, alkaloids, flavonoids, saponins, and phenols. This study aims to determine the antibacterial activity of the methanol extract of E. hirta against R. solanacearum, E. coli and S. aureus. The extraction method of E. hirta was maceration with methanol solvent, while antibacterial activity test using the agar diffusion method (Kirby-Bauer) with test bacteria was R. solanacearum, E. coli and S. aureus. E. hirta extract tested was pure extract (100%). Observed response was diameter of inhibitory zone formed around the paper discs that had been smeared with E. hirta extract on the media. Analysis of the data using a Completely Randomized Design (CRD) 1 factor (test bacteria) with three times repetition, followed by a further test of Duncan with 95% confidence level. The results indicated that E. hirta produced extraction yield of 6,45%. Antibacterial activity of E. hirta extract against R. solanacearum, E. coli and S. aureus was indicated by Inhibitory Zone Diameter (HZD), respectively for 21,8 mm, 18,26 mm and 17,06 mm. The results of this study showed that the methanol extract of E. hirta plant had antibacterial activity against R. solanacearum, E. coli and S. aureus, thus can be used as a biocontrol agent of bacterial wilt disease in plants caused by R. solanacearum and human disease caused by E. coli and S. aureus. Keywords: Euphorbia hirta, Ralstonia solanacearum, Escherichia coli, Staphylococcus aureus, antibacterial activity, diffusion method